The effects of body dissatisfaction and depression levels on the dietary habits of university students in southern China during COVID-19 - Wu, Chunmei; Hao, Ming; Liu, Xuesheng; Yang, Di; Liu, Bang; Yan, Wenjing; Wang, Qi (Frontiers in Nutrition, 2023)
The novel coronavirus disease of 2019 has impacted people's lives greatly. The spread of the pandemic has restricted many everyday social lives. Some studies have shown that strict risk control during the pandemic threatens people's mental health and eating habits. University students vulnerable to mental health problems may have more prominent mental health and eating disorders during the pandemic. This study aims to elucidate the relationship between body dissatisfaction, depression, body mass index, and emotional eating among university students in the context of the pandemic in southern China. It provides a theoretical basis for developing future approaches to improve depression and emotional eating among university students. A total of 1135 university students were recruited for the study. All participants completed anthropometric, body dissatisfaction, eating behavior, and depression level surveys. The study finds that female students have higher levels of body dissatisfaction, depression, and emotional eating than male students. University students in the high body dissatisfaction group had higher levels of depression.Depression level (β=0.33, p<0.01), body dissatisfaction (β=0.22, p<0.01), sex (β=0.16, p<0.01), and income (β=0.06, p<0.01) were significant predictors of emotional eating. Fundamentally, this study highlights the impact of body dissatisfaction on depression and emotional eating. The potential to improve depression and emotional eating among university students by improving their levels of body dissatisfaction was demonstrated.